2012
DOI: 10.1681/asn.2011080851
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte TIMP3 and ADAMTS1 Modulate Vascular Stability after Kidney Injury

Abstract: Kidney pericytes are progenitors of scar-forming interstitial myofibroblasts that appear after injury. The function of kidney pericytes as microvascular cells and how these cells detach from peritubular capillaries and migrate to the interstitial space, however, are poorly understood. Here, we used an unbiased approach to identify genes in kidney pericytes relevant to detachment and differentiation in response to injury in vivo, with a particular focus on genes regulating proteolytic activity and angiogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
191
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(200 citation statements)
references
References 66 publications
7
191
0
Order By: Relevance
“…PDGFRβ/PDGF-BB is the main signalling pathway mediating pericyte recruitment during vessel development (Hellstrom et al, 1999). This same pathway has been reported in the recruitment of pericytes to injured tissue, where they eventually contribute to fibrosis in organs such as the lung (Hung et al, 2013) and kidney (Humphreys et al, 2010;Lin et al, 2011;Schrimpf et al, 2012). Activated pericytes have been shown to detach from local capillaries, migrate to the site of injury and differentiate into myofibroblasts (Goritz et al, 2011;Lin et al, 2011;Ren et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurysupporting
confidence: 60%
See 2 more Smart Citations
“…PDGFRβ/PDGF-BB is the main signalling pathway mediating pericyte recruitment during vessel development (Hellstrom et al, 1999). This same pathway has been reported in the recruitment of pericytes to injured tissue, where they eventually contribute to fibrosis in organs such as the lung (Hung et al, 2013) and kidney (Humphreys et al, 2010;Lin et al, 2011;Schrimpf et al, 2012). Activated pericytes have been shown to detach from local capillaries, migrate to the site of injury and differentiate into myofibroblasts (Goritz et al, 2011;Lin et al, 2011;Ren et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurysupporting
confidence: 60%
“…However, the recruitment of pericytes following injury and their collagen-producing capacity may be dependent on both the type of injury and the tissue under investigation (Birbrair et al, 2014a;Nakagomi et al, 2011). Activated pericytes have been shown to upregulate genes associated with migration, for example ADAMTS1 and TIMP3 (Hung et al, 2013;Schrimpf et al, 2012). Furthermore, the increased motility of these cells is coordinated by the upregulation of ADAMTS1 peptidase and downregulation of TIMP3 (Schrimpf et al, 2012).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…The 45 But, compared to the well-established general models for pericyteendothelial coordination during embryogenesis, far less is understood of how lung pericytes act on the vasculature during homeostasis, degeneration, or regeneration. 5,6,18 The receptor, PDGFR-b, marks pericytes and establishes their interactions with endothelial cells.…”
Section: Lung Pericytes and Resident Fibroblastsmentioning
confidence: 99%
“…Recent studies have identified a critical connection between PTC rarefaction and the development of interstitial fibrosis of the kidney. 4,5 Kidney pericytes are an extensive population of mesenchyme-derived cells that are attached to endothelial cells (ECs) of PTCs where they perform vascular stabilizing and regulatory functions. [4][5][6][7][8][9] However, in response to sustained injury, pericytes detach themselves from ECs and become scar-forming myofibroblasts, while simultaneously losing normal pericyte functions.…”
mentioning
confidence: 99%